Enzymatic cocktails produced by Fusarium graminearum under submerged fermentation using different lignocellulosic biomasses. Issue 2 (29th May 2014) - Debeire, Philippe; Delalande, Francois; Habrylo, Olivier; Jeltsch, Jean‐Marc; Van Dorsselaer, Alain; Phalip, Vincent
Abstract Fusarium graminearum was grown on four lignocellulosic substrates (corn cobs, wheat bran, hop cell walls, and birchwood) and glucose as the sole carbon source. Proteomic studies performed on the resulting enzymatic cocktails highlighted a great diversity in the number and type of proteins secreted. The cell wall‐degrading enzymes (CWDE) proportion varied greatly from 20% to 69%. Only one of the 57 CWDEs detected in this study was common to the five proteomes. In contrast, 35 CWDEs were specific to one proteome only. The polysaccharide‐degradation activities were different depending on the cocktail and the polysaccharide used. F. graminearum strongly modifies the enzymatic cocktail it secretes as a function of the biomass used for growth.